Characteristics of KIPT staff by groups of radiation risk - Dovbnya, A.N.; Mazilov, A.V.; Stadnik, I.A. (Вопросы атомной науки и техники, 2014)
The methodology of individual radiation cancer risk assessment UNSCEAR-94 has been described. Characteristics
of KIPT staff at the individual monitoring, in terms of the "Dose-response matrix" have been reviewed. The main results
of the calculations of the relative, attributive and absolute radiation risks of KIPT personnel for different sites and
different risk groups have been showed. The distributions of the main characteristics of the personnel: age, years on the
individual monitoring and the cumulative dose for different radiation risk groups of staff have been investigated. Описана методология проведения оценки индивидуальных радиационных рисков для пролонгированного облучения UNSCEAR-94. Дана характеристика персонала ННЦ ХФТИ, состоящего на ИДК, в терминах «дозовой матрицы». Приведены основные результаты расчетов относительного, атрибутивного и абсолютного радиационных рисков персонала ННЦ ХФТИ для различных локализаций и различных групп риска. Показаны распределения основных характеристик персонала: возраста, стажа на ИДК и накопленной дозы для различных групп радиационного риска персонала. Описано методологію проведення оцінки індивідуальних радіаційних ризиків для пролонгованого опромінення UNSCEAR-94. Надана характеристика персоналу ННЦ ХФТІ, що перебуває на ІДК, в термінах «дозової матриці». Наведено основні результати розрахунків відносного, атрибутивного й абсолютного радіаційних ризиків персоналу ННЦ ISSN 1562-6016. ВАНТ. 2014. №3(91) 208 ХФТІ для різних локалізацій і різних груп ризику. Показано розподіл основних характеристик персоналу: віку, стажу на ІДК і накопиченої дози для різних груп радіаційного ризику персоналу.